The first record of grass-like fern, Schizaea dichotoma (L.) J. Sm. (Schizaeaceae) from Lingga Island, Indonesia: Its morphological, anatomical and palynological study - Nery Sofiyanti; DYAH IRIANI Iriani; FITMAWATI Fitmawati (Society for Indonesian Biodiversity, 2019)
Abstract. Sofiyanti N, Iriani D, Fitmawati. 2019. The first record of grass-like fern, Schizaea dichotoma (L.) J. Sm. (Schizaeaceae) from Lingga Island, Indonesia: Its morphological, anatomical and palynological study. Biodiversitas 20: 2651-2660. Schizaea dichotoma (L.) J.Sm. is one of fern species from Family Schizaeaceae. This species is grass-like, dimorphic with fan-shaped fronds, and well-known with local name Rumput Merak. The first record of this species is reported from Lingga Island, Riau Islands Province, Indonesia. The aim of this study was to examine the morphology, anatomy and spore characteristics of this fern. This study had been carried from June to December 2017. Samples were collected using exploration method, documented, and prepared for herbarium specimen. In this study, we examined the morphological characters, anatomical characters of rhizome, stipes, and pinnae of both fertile and sterile fronds, as well as spore feature. The anatomical preparations were carried out using paraffin method, while spore specimens using acetolysis method. The anatomy of rhizome, stipes, and pinnae, as well as spore characters, were then observed and documented using digital microscope Celeron. S. dichotoma is dimorphic fern with grass-like habit, fan-shaped laminae that repeatedly forked end in sorospore in fertile frond. The rhizome has vascular bundle surrounded by star-shaped sclerenchymatous layer. The cross-section of stipes of both fertile and sterile fronds are